2021
DOI: 10.1080/2162402x.2021.1900508
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structures and B lymphocytes in cancer prognosis and response to immunotherapies

Abstract: Tertiary lymphoid structures (TLS) are ectopic cellular aggregates that resemble secondary lymphoid organs in their composition and structural organization. In contrast to secondary lymphoid organs, TLS are not imprinted during embryogenesis but are formed in non-lymphoid tissues in response to local inflammation. TLS structures exhibiting a variable degree of maturation are found in solid tumors. They are composed of various immune cell types including dendritic cells and antigen-specific B and T lymphocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 158 publications
1
26
1
Order By: Relevance
“… 42 43 Although the predictive role of HEV in ICI has been less investigated, the tertiary lymphoid structure, which is an ectopic lymphoid structure with abundant HEV, was found to be a favorable biomarker for ICI therapy. 44 However, HEV was not always associated with the organized lymphoid structure and was often present within the loosely assembled lymphoid aggregates. 45 Moreover, HEV was a significant prognostic factor for RFS and OS in our study (data not shown), regardless of CLR, which resembles the tertiary lymphoid structure.…”
Section: Discussionmentioning
confidence: 99%
“… 42 43 Although the predictive role of HEV in ICI has been less investigated, the tertiary lymphoid structure, which is an ectopic lymphoid structure with abundant HEV, was found to be a favorable biomarker for ICI therapy. 44 However, HEV was not always associated with the organized lymphoid structure and was often present within the loosely assembled lymphoid aggregates. 45 Moreover, HEV was a significant prognostic factor for RFS and OS in our study (data not shown), regardless of CLR, which resembles the tertiary lymphoid structure.…”
Section: Discussionmentioning
confidence: 99%
“… 25 TLS were defined as aggregates of lymphocytes with formation of a lymphoid based on hematoxylin and eosin stain and were counted with frequency/mm 2 . 26 …”
Section: Methodsmentioning
confidence: 99%
“…NSCLC are often associated with the presence of 'Tertiary Lymphoid Structures' (TLS). TLS may occur at both the margins and the core of tumors, are spatially well-organized and are composed of T and B cell zones and germinal centers (51). Some authors have correlated the presence of B cells in TLS with favorable outcomes (52)(53)(54)(55)(56).…”
Section: Tertiary Lymphoid Structuresmentioning
confidence: 99%